PERAN HUMAN CAPITAL, TRANSFORMASIONAL LEADERSHIP TERHADAP SUSTAINABLE CORPORATE: SUSTAINABLE HUMAN RESOURCES MANAGEMENT SEBAGAI VARIABEL MEDIASI - NURTI WIDAYATI; DITA OKI BERLIYANTI; B. MEDINA NILASARI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The study aims to prove the direct impact of Human Capital and Transformational Leadership on sustainable corporate practices, as well as the indirect impact of Human Capital and Transformational Leadership on sustainable corporate practices through Human Resources Management. The research employs a questionnaire method with a total sample size of 62 and uses SmartPLS to test the direct and indirect effects of Human Capital and Transformational Leadership on sustainable corporate practices. The results confirm both direct and indirect effects of the two variables, meaning this study provides relevant implications for the field of education by emphasizing the improvement of Human Capital and Transformational Leadership for sustainable corporate practices to avoid falling behind.